2015
DOI: 10.1038/ncomms7118
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent ARID1A–PIK3CA mutations promote ovarian clear-cell tumorigenesis through pro-tumorigenic inflammatory cytokine signalling

Abstract: Ovarian clear-cell carcinoma (OCCC) is an aggressive form of ovarian cancer with high ARID1A mutation rates. Here we present a mutant mouse model of OCCC. We find that ARID1A inactivation is not sufficient for tumor formation, but requires concurrent activation of the phosphoinositide 3-kinase catalytic subunit, PIK3CA. Remarkably, the mice develop highly penetrant tumors with OCCC-like histopathology, culminating in hemorrhagic ascites and a median survival period of 7.5 weeks. Therapeutic treatment with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
246
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(265 citation statements)
references
References 67 publications
(104 reference statements)
11
246
1
3
Order By: Relevance
“…30 Moreover, a recent pre-clinical study has shown that additional loss of ARID1A function in the setting of PIK3CA overexpression is a key step in pathogenesis of OCCC. 31 Interestingly, IL-6 transcription in this OCCC model of ARID1A and PIK3CA mutation is found to be elevated. Therefore, it is paramount to see if this correlation seen in pre-clinical study also exists in human samples of OCCC by sequencing ARID1A and PIK3CA correlating with plasma IL-6 level.…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, a recent pre-clinical study has shown that additional loss of ARID1A function in the setting of PIK3CA overexpression is a key step in pathogenesis of OCCC. 31 Interestingly, IL-6 transcription in this OCCC model of ARID1A and PIK3CA mutation is found to be elevated. Therefore, it is paramount to see if this correlation seen in pre-clinical study also exists in human samples of OCCC by sequencing ARID1A and PIK3CA correlating with plasma IL-6 level.…”
Section: Discussionmentioning
confidence: 99%
“…ARID1A has been reported to interact with SIN3A to suppress transcription of genes involved in cell cycle regulation and tumor progression such as c-Myc, cdc2, cyclin E, cyclin A, and IL-6 (12,35,38). Here, our ChIP analysis demonstrated an increase of promoter occupancy by SIN3A in ARID1A-induced cells as compared with noninduced cells (Fig.…”
Section: Arid1a Associates With Sin3a Co-repressor and Repressivementioning
confidence: 99%
“…At the molecular level, our previous study demonstrated that the ARID1A complex interacted and collaborated with p53 to regulate transcription of several effectors including CDKN1A encoding p21 (8). In genetically engineered mice, whereas Arid1a deletion by itself is insufficient to transform cells, codeletion of Arid1a with either Pten or Pik3ca is required to drive the formation of ovarian endometrioid and clear cell-like carcinomas, respectively (11,12).…”
mentioning
confidence: 99%
“…Význam mutace genu ARID1A pro tento typ ovariálních karcinomů potvrzují i myší modely. Inaktivace genů ARID1A a PIK3CA vedla k indukci clear cell karcinomů ovaria, zatímco inaktivace PTEN a ARID1A vedla k vytváření endometrioidních karcinomů [36,37]. Současné práce ukazují, že ARID1A může fungovat jako nádo-rový supresor i jako housekeeping gen. Mutace ARID1A vede k indukci exprese onkogenů PI3K a AKT a naopak ke snížení exprese genu kódujícího protein MLH1, který je zodpovědný za MMR.…”
Section: Arid1aunclassified